The Impact of Modular Professional Nursing Care Model (Modification of The Primary-Team Model) on Patient Satisfaction in Health Services: A Literature Review - Nugrahini, Ni Luh Gede Hari; Suyasa, I Gede Putu Darma; Adianta, I Ketut Alit; Agustini, Ni Komang Tru (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
Optimal health services are considerably increasing patient satisfaction. Optimization of health services could be implemented using the Modular Professional Nursing Care Method (MAKP Modular). MAKP Modular provides a clear division of tasks and responsibilities for nurses in accordance with the distribution of nursing staff. This literature review aimed to identify the effect of MAKP Modular in increasing patient satisfaction through the optimization of health services. The research design is a literature review. The journal article was conducted on the Google Scholar journal database website and 10 journal articles were selected according to inclusion criteria. The results of the review show that the application of MAKP Modular affects the quality of implementation of nursing care standards. The performance of nurses manifested in the implementation of MAKP Modular also influences patient satisfaction. However, there are still some deficiencies in the application of modular MAKP in the health service setting. These deficiencies are influenced by factors of knowledge, attitudes, and motivation of nurses. The application of MAKP Modular to the healthcare system is conducted by combining the team method and the primary method. The combination of these two methods allows for a more effective and efficient process of providing nursing care. Evaluation of the implementation of MAKP Modular in clinical and hospital settings needs to be engaged on an ongoing basis to determine the effectiveness of implementation.